Implementasi Penilaian Kinerja Guru di SMK Muhammadiyah 3 Surakarta - Tarmo (Nur Science Institute, 2021)
Aim of the research are to describe the implementation of teacher performance assessment, supporting, and inhibiting factors of teacher performance assessment at SMK Muhammadiyah 3 Surakarta. This type of research is a qualitative research with a case study design. Data collection are done by in-depth interview, observation and documentation. Data analysis using an interactive analysis model. The results of the study concluded that 1) The implementation of teacher performance assessment at SMK Muhammadiyah 3 Surakarta is held once a year periodically divided into two activities, namely the teacher's self evaluation period and the assessment period. Teacher performance assessment methods are carried out through observation and monitoring. The implementation of Teacher Performance Assessment at SMK Muhammadiyah 3 Surakarta in 2017 and 2018 has increased from the Fair category to the Good category. 2) Factors that support teacher performance assesment at SMK Muhammadiyah 3 Surakarta are good coordination between the principal, the assessment team, and teacher, the effectiveness of the teacher in carrying out learning, and the teacher has participated in educational equalization activities. 3) Inhibiting factors of teacher performance assesment at SMK Muhammadiyah 3 Surakarta are the lack of operational funding support from the government, Teacher Performance Assessment schedules that conflict with other activities, and time constraints.